Differential factors associated with challenge‐proven food allergy phenotypes in a population cohort of infants: a latent class analysis. Issue 5 (16th April 2015) - Peters, R. L.; Allen, K. J.; Dharmage, S. C.; Lodge, C. J.; Koplin, J. J.; Ponsonby, A.‐L.; Wake, M.; Lowe, A. J.; Tang, M. L. K.; Matheson, M. C.; Gurrin, L. C.; ,
Summary: Background: Food allergy, eczema and wheeze are early manifestations of allergic disease and commonly co‐occur in infancy although their interrelationship is not well understood. Data from population studies are essential to determine whether there are differential drivers of multi‐allergy phenotypes. We aimed to define phenotypes and risk factors of allergic disease using latent class analysis (LCA). Methods: The HealthNuts study is a prospective, population‐based cohort of 5276 12‐month‐old infants in Melbourne, Australia. LCA was performed using the following baseline data collected at age 12 months: food sensitization (skin prick test ≥ 2 mm) and allergy (oral food challenge) to egg, peanut and sesame; early (< 4 months) and late‐onset eczema; and wheeze in the first year of life. Risk factors were modelled using multinomial logistic regression. Results: Five distinct phenotypes were identified: no allergic disease (70%), non‐food‐sensitized eczema (16%), single egg allergy (9%), multiple food allergies (predominantly peanut) (3%) and multiple food allergies (predominantly egg) (2%). Compared to the baseline group of no allergic disease, shared risk factors for all allergic phenotypes were parents born overseas (particularly Asia), delayed introduction of egg, male gender (except for single egg allergy) and family history of allergic disease, whilst exposure to pet dogs was protective for all phenotypes. Other factors including filaggrin mutations, vitamin D and the presence of older siblings differed by phenotype. Conclusions and clinical relevance: Multiple outcomes in infancy can be used to determine five distinct allergy phenotypes at the population level, which have both shared and separate risk factors suggesting differential mechanisms of disease.